How Audiences Engage With Drama: Identification, Attribution and Moral Approval - Teasdale, Ben; Maguire, Laurie; Budelmann, Felix; Dunbar, R. I. M. (Frontiers in Psychology, 2021)
Fictional storytelling has played an important role in human cultural life since earliest times, and we are willing to invest significant quantities of time, mental effort and money in it. Nonetheless, the psychological mechanisms that make this possible, and how they relate to the mechanisms that underpin real-world social relationships remain understudied. We explore three factors: identification (the capacity to identify with a character), moral approval, and causal attribution with respect to a character’s behaviour in live performances of two plays from the European literary canon. There were significant correlations between the extent to which subjects identified with a character and their moral approval of that character’s behaviour that was independent of the way the play was directed. However, the subjects’ psychological explanations for a character’s behaviour (attribution) were independent of whether or not they identified with, or morally approved of, the character. These data extend previous findings by showing that moral approval plays an important role in facilitating identification even in live drama. Despite being transported by an unfolding drama, audiences do not necessarily become biased in their psychological understanding of why characters behaved as they did. The psychology of drama offers significant insights into the psychological processes that underpin our everyday social world.